2011
DOI: 10.1539/joh.11-0023-oa
|View full text |Cite
|
Sign up to set email alerts
|

Association between Job Stress and Newly Detected Combined Dyslipidemia among Chinese Workers: Findings from the SHISO Study

Abstract: Previous studies examining the association between job stress and blood lipids have produced mixed findings. We sought to investigate the association between job stress and blood lipids among Chinese workers. Methods: A total of 544 subjects (367 men and 177 women) without known diseases from the Stress and Health in Shenzhen Workers (SHISO) cross-sectional study were analyzed. Job stress was evaluated by the effort-reward imbalance (ERI) model. The associations between job stress and blood lipids, such as for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
(46 reference statements)
3
26
0
2
Order By: Relevance
“…However, in our study, the pattern of results was similar in women and men. Therefore, we do not expect that the effect of smoking as a potential confounder would be powerful enough to substantially change the results, as described previously [Xu et al, 2010a[Xu et al, , 2011a. (iv), In this study, job stress was assessed only one time, which may result in misclassification of chronic exposure and bias results towards the null value [Kivimaki et al, 2006].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, in our study, the pattern of results was similar in women and men. Therefore, we do not expect that the effect of smoking as a potential confounder would be powerful enough to substantially change the results, as described previously [Xu et al, 2010a[Xu et al, , 2011a. (iv), In this study, job stress was assessed only one time, which may result in misclassification of chronic exposure and bias results towards the null value [Kivimaki et al, 2006].…”
Section: Discussionmentioning
confidence: 83%
“…ERI is associated with increased risk of coronary heart disease [Xu et al, 2009;Xu et al, 2010b], and risk of recurrent acute myocardial infarction [Aboa-Eboule et al, 2011]. Previous studies have also documented that ERI is associated with subclinical atherosclerosis [Xu et al, 2010a] and risk factors of CVD, such as hypertension [Xu et al, 2013], dyslipidemia [Xu et al, 2011a], and diabetes mellitus .Recently, studies reveal that the immune system plays important roles in the pathway from chronic psychosocial stress to disease [Nakata, 2012]. There is growing evidence demonstrating the role of inflammation in the immune system during the development of CVD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Foundational research in this area reported higher A1c among adult male workers without diabetes exposed to workplace stress (i.e., noise, rotating shifts, overwork) compared to peers not exposed to those chronic job stressors [56]. In a more recent study of Chinese workers without diabetes or impaired glucose tolerance, Xu and colleagues [57] reported a relationship between A1c and job stress in women, but not men. Chronic financial strain over a 10-year period has also been associated with high A1c levels in African-American women without diabetes [58].…”
Section: Mechanisms and Buffers Of The Stress-a1c Associationmentioning
confidence: 99%
“…ERI has been shown to predict poor health in numerous studies [14] and has been linked to CVD incidence and mortality [14][15][16][17]. Indeed, some research has linked ERI to individual MetS components, i.e., hypertension [18], dyslipidemia [19] and (pre-)diabetes [20].…”
Section: Introductionmentioning
confidence: 99%